2017
DOI: 10.1088/1361-648x/aa53a6
|View full text |Cite
|
Sign up to set email alerts
|

Vortices and vortex lattices in quantum ferrofluids

Abstract: The experimental realization of quantum-degenerate Bose gases made of atoms with sizeable magnetic dipole moments has created a new type of fluid, known as a quantum ferrofluid, which combines the extraordinary properties of superfluidity and ferrofluidity. A hallmark of superfluids is that they are constrained to rotate through vortices with quantized circulation. In quantum ferrofluids the long-range dipolar interactions add new ingredients by inducing magnetostriction and instabilities, and also affect the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 315 publications
(708 reference statements)
3
53
0
Order By: Relevance
“…This discovered, QFM or else Quantum Magnet, vortex flux could also provide a possible physical mechanism for explaining the macroscopic field imprint of magnetic dipoles as shown in fig.2. The effect is similar as described by vortex hydrodynamics [18][19][20], quantum Bose-Einstein condensate ferrofluids [21] and general vortex model theory [22,23] very often encountered in nature from the quantum scale to the macro world [13]. The quantum vortex flux we call, M-field shown in fig.2(a) with red and fig.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…This discovered, QFM or else Quantum Magnet, vortex flux could also provide a possible physical mechanism for explaining the macroscopic field imprint of magnetic dipoles as shown in fig.2. The effect is similar as described by vortex hydrodynamics [18][19][20], quantum Bose-Einstein condensate ferrofluids [21] and general vortex model theory [22,23] very often encountered in nature from the quantum scale to the macro world [13]. The quantum vortex flux we call, M-field shown in fig.2(a) with red and fig.…”
Section: Resultsmentioning
confidence: 56%
“…The ferrolens optic display device is an electric insulator at all temperatures therefore not a superconductor. In addition we tested rigorously for superfluidic behavior concerning quantization of magnetic vortices generation at different values of induced angular momentum [21] [39] without any observable effect.…”
Section: Quantum Magnetmentioning
confidence: 99%
“…Finally, by t = 5000ω −1 ⊥ the vortices have entered the condensate and have relaxed into a triangular Abrikosov vortex lattice. Several theoretical studies have indicated that this may be the ground state for a system of vortices in (non-)dipolar BECs at finite rotation frequencies [35,36,38,42,43,46,70]. In nondipolar BECs subject to a ramping up of the trapping rotation frequency, a vortex lattice is seen to form following a period of evolution of the nondipolar GPE at constant rotation frequency after the vortex instability has been triggered [66,71].…”
Section: Dipolar Gross-pitaevskii Equation Simulationsmentioning
confidence: 99%
“…Examples of the methods that experimentalists have used to create vortices include: direct imprinting of phase defects into the condensate [29], rotation of either a laser * srivatsa.badariprasad@unimelb.edu.au beam stirrer or the external trapping potential of the condensate itself [30,31], dragging a barrier through the condensate [27,28,32], applying a rapidly oscillating perturbation to the trapping potential [25], Bose-condensing a rotating normal Bose gas [33], and utilising the Kibble-Zurek mechanism to trigger the formation of topological defects [34]. While vortices have not yet been experimentally observed in dipolar BECs, there exists an extensive body of theoretical research regarding vortex structure, vortex lattice structure, and vortex-vortex interactions in these systems [35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Dipolar Bose-Einstein condensates (BECs) have proved to be a unique, highly-controllable platform for studying the interplay of quantum many-body physics and magnetic interactions [1][2][3][4][5][6]. Compared to conventional condensates, in which the atoms undergo shortrange, contact-like, isotropic inter-particle interactions, a dipolar BEC also enjoys a long-range anisotropic dipoledipole interaction (DDI) [7][8][9][10][11]. While the first dipolar BECs were realised in a gas of 52 Cr [1,2], atoms with larger magnetic dipole moments such as 164 Dy [4,6] and 168 Er [5] have now been cooled to form strongly dipolar BECs.…”
mentioning
confidence: 99%